2007
DOI: 10.1074/jbc.m608234200
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Acidic Residues in Helix II Stabilizes the Folded Conformation of Acyl Carrier Protein and Variably Alters Its Function with Different Enzymes

Abstract: Acyl carrier protein (ACP), a small protein essential for bacterial growth and pathogenesis, interacts with diverse enzymes during the biosynthesis of fatty acids, phospholipids, and other specialized products such as lipid A. NMR and hydrodynamic studies have previously shown that divalent cations stabilize native helical ACP conformation by binding to conserved acidic residues at two sites (A and B) at either end of the "recognition" helix II. To examine the roles of these amino acids in ACP structure and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…Strategic placement of basic residues in ACP can influence its solution conformation; e.g., mutation of Ala-75 to His results in a more compact helical ACP at neutral°pH°due°to°charge°neutralization° [24].°Recently, we have shown that site-directed mutagenic neutralization of seven acidic divalent cation-binding residues at both ends of Helix II also increases helical content and decreases°the°hydrodynamic°radius°of°ACP° [26].°This ACP mutant (SA/SB) is expressed predominantly in the apo-form and cannot be further stabilized by divalent cation°binding.°As°shown°in°Figure°1c,°apo-SA/SB exhibited significantly greater helical content than aporACP at neutral pH and was only slightly unfolded even at pH 9.5. However, the CSD of this mutant exhibited only a modest change over this pH range, with average net charge decreasing from 8.0 at pH 9.5 to 7.6°at°pH°4.4°(Figure°2b).°Moreover,°this°profile°was very similar to that of rACP, consistent with earlier observations that the CSD of a protein does not necessarily°reflect°its°net°charge°in°solution° [15],°which°in°this case would be considerably lower for SA/SB (total of 15 acidic residues) relative to rACP (22 acidic residues) at neutral and higher pH values.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Strategic placement of basic residues in ACP can influence its solution conformation; e.g., mutation of Ala-75 to His results in a more compact helical ACP at neutral°pH°due°to°charge°neutralization° [24].°Recently, we have shown that site-directed mutagenic neutralization of seven acidic divalent cation-binding residues at both ends of Helix II also increases helical content and decreases°the°hydrodynamic°radius°of°ACP° [26].°This ACP mutant (SA/SB) is expressed predominantly in the apo-form and cannot be further stabilized by divalent cation°binding.°As°shown°in°Figure°1c,°apo-SA/SB exhibited significantly greater helical content than aporACP at neutral pH and was only slightly unfolded even at pH 9.5. However, the CSD of this mutant exhibited only a modest change over this pH range, with average net charge decreasing from 8.0 at pH 9.5 to 7.6°at°pH°4.4°(Figure°2b).°Moreover,°this°profile°was very similar to that of rACP, consistent with earlier observations that the CSD of a protein does not necessarily°reflect°its°net°charge°in°solution° [15],°which°in°this case would be considerably lower for SA/SB (total of 15 acidic residues) relative to rACP (22 acidic residues) at neutral and higher pH values.…”
Section: Resultsmentioning
confidence: 94%
“…Myristoyl-ACP was prepared enzymatically from holo-ACP by incubation with myristic acid (14:0), ATP, and V. harveyi acyl-ACP synthetase as detailed elsewhere [25]. Site-directed mutagenesis of rACP and preparation of mutant SA/SB, in which seven central conserved acidic amino acid residues are replaced with their corresponding neutral amide residues, is described in reference [26].°Similar methods were used to replace Leu at position 46 with Trp to introduce an intrinsic fluorescence probe sensitive to ACP folding (Gong and Byers, manuscript in preparation). Residue numbering corresponds to that of native V. harveyi ACP (SwissProt accession no.…”
Section: Methodsmentioning
confidence: 99%
“…This region is already known to be recognized by a number of enzymes, e.g. ␤-ketoacyl-(ACP) reductase (37,38), acyl carrier protein synthase (39), protein acyltransferase HlyC (40), acyl-ACP synthetase, UDP-N-acetyl glucosamine acyltransferase (41), and ␤-ketoacyl-ACP synthase III (42). Outward movement of helix III in combination with acyl chain insertion generates strain on the ACP molecule, as revealed from slight changes in C ␣ and C ␤ of residues present at the bottom opening of the hydrophobic core in tetradecanoyl-ACP.…”
Section: Phosphopantetheine Moiety Is Relatively Structured In the Acmentioning
confidence: 99%
“…To further examine the effect of cyclization on ACP structure in solution, we used a variety of biophysical methods to analyze the conformation of both cycL46W and linL46W in response to Mg 2ϩ ions, which are known to induce a folded helical conformation upon binding to V. harveyi ACP at physiological pH (10). The apo forms of linear ACPs were used in these studies, as cyclic ACP is predominantly expressed in this form (see below).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Vibrio harveyi ACP is largely unfolded at neutral pH, but its helical conformation can be stabilized by charge neutralization (i.e. at low pH or by residue replacements) (13), by binding of divalent cations to helix II (10), or by interaction with partner enzymes (15). Molecular dynamic simulations (16) and NMR experiments (17,18) have indicated greatest mobility in the long loop I connecting helices I and II, in the helix II-helix III region, and at the N and C termini, which are in close proximity.…”
Section: Bacterial Acyl Carrier Protein (Acp)mentioning
confidence: 99%